2018
DOI: 10.3390/molecules23051225
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Aspects of the O-acetylation of C-tetra(phenyl)calixpyrogallol[4]arene

Abstract: Reaction between pyrogallol and benzaldehyde results in a conformational mixture of C-tetra(phenyl)pyrogallol[4]arene (crown and chair). The conformer mixture was separated using crystallization procedures and the structures were determined using FTIR, 1H-NMR, and 13C-NMR. O-acetylation of C-tetra(phenyl)pyrogallol[4]arene (chair) with acetic anhydride, in pyridine results in the formation of dodecaacetyl-tetra(phenyl)pyrogallol[4]arene. The structure was determined using 1H-NMR and 13C-NMR finding that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Polyhydroxylated platforms such as calixarenes, resorcinarenes, or pyrogalloarenes (Figure 1) are a very interesting class of compounds. They have a remarkable ability to act as receptors for a variety of guest species, depending on their structural properties [23,24,25,26,27], which can be modified by changing the size of the substituents or by adding functional groups as a part of the scaffold [28,29,30,31,32]. Among the described macrocyclic compounds, calixarenes are probably the most promising for application in the area of host–guest recognition of toxicological molecules.…”
Section: Calix[n]arenesmentioning
confidence: 99%
“…Polyhydroxylated platforms such as calixarenes, resorcinarenes, or pyrogalloarenes (Figure 1) are a very interesting class of compounds. They have a remarkable ability to act as receptors for a variety of guest species, depending on their structural properties [23,24,25,26,27], which can be modified by changing the size of the substituents or by adding functional groups as a part of the scaffold [28,29,30,31,32]. Among the described macrocyclic compounds, calixarenes are probably the most promising for application in the area of host–guest recognition of toxicological molecules.…”
Section: Calix[n]arenesmentioning
confidence: 99%
“…Continuing with our studies of the structure of polyhydroxylated platforms [12,33,40,41], we found that the bulky aromatic substituents on the lower rim of polyhydroxylated platforms in cone conformation exhibited a dynamic behavior, which stimulated interest in examining the conformational preferences. For this purpose, in this article, the comparative behavior of Ctetra(phenyl)-resorcin [4]arene (1) and C-tetra(phenyl)pyrogallol [4]arene (2) compounds is studied using 1 H-NMR and 13 C-NMR data and dynamic 1 H-NMR spectra.…”
Section: Synthesis and Separation Of Conformersmentioning
confidence: 54%
“…On the other hand, those synthesized from aromatic aldehydes show a preference for producing chair-type isomers [10,11]. Even so, as with resorcinarenes, there are some cases where the tendency changes or an isomeric mixture is produced, depending on the synthesis conditions [12].…”
Section: Scheme 1 Synthesis Of Resorcinarenes and Pyrogallolarenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calixarenes offer several possibilities for non-covalent interactions. The first possibility is due to their bowl-shaped which provides a π-electron rich cavity [74]. The binding interactions that take place in this cavity could be, π-system type with inorganic and organic cations or polar-π and CH-π with neutral molecules.…”
Section: Calixarenes and Analoguesmentioning
confidence: 99%